Is parricide a stable phenomenon? An analysis of parricide offenders in a forensic hospital (2017)
Introduction: Previous research has shown that severe mental illness is prevalent among parricide offenders.Objective: To investigate sociodemographic and psychiatric characteristics, killing methods and criminal background of parricide offenders admitted into a forensic inpatient mental health facility in Brazil.Materials and methods: Sample consisting of patients charged with parricide under psychiatric care in the Forensic Psychiatric Hospital. A cross-sectional analysis of the sociodemographic variables of parricide offenders and their victims, crime characteristics and psychiatric diagnosis of perpetrators was carried out.Results: Most parricides were young (mean age=29.2;SD=9.4) and had little or no formal schooling (mean=5.4;SD=3.9); 100% were adult males, 94.4% (n=17) were single, and 77.8%(n=14) did not have prior convictions. All offenders acted alone, predominantly against elderly victims (mean=63.3;SD=13.2), at their parent’s household (n=15; 83.3%), and only one used firearms; 55.6% (n=10) were patricides, 5.6% (n=1) step-patricides, 33.3% (n=6) matricides, and 5.6% (n=1) double parricides. After perpetrating the crime, 27.8% (n=5) attempted to escape the scene. Most perpetrators suffered schizophrenia (n=11;61.1%) or had an antisocial personality (n=3;16.7%).Conclusions: Regarding weapon usage and the characteristics of victims and offenders, the observed pattern is consistent with previous researches, which allows concluding that the phenomenon of parricide is relatively stable and homogeneous. A forensic psychiatric evaluation of parricide offenders should be warranted given the high prevalence of mental illness among them.